2009
DOI: 10.1007/s11357-009-9095-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic 17β-estradiol treatment improves skeletal muscle insulin signaling pathway components in insulin resistance associated with aging

Abstract: Insulin resistance is a common feature of aging in both humans and rats. In the case of females, it seems to be related to loss of gonadal function, due mainly due to a decrease in plasma estrogen levels. Several causes have been postulated for this insulin resistance, among them changes in several steps of the insulin pathway. In view of these findings, the purpose of the present study was to examine the role of chronic 17β-estradiol treatment on insulin sensitivity during the aging process, and its effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Results from previous studies have indicated that estrogens increase insulin sensitivity and stimulate glucose uptake upon acute and chronic exposure to these steroids in target tissues as well as in ESR1-positive breast cancer cells (Alonso et al 2006, Moreno et al 2010, Garrido et al 2013. On the basis of these findings and considering that GPER1 has been shown to be involved in insulinregulated metabolic functions in both mice and humans (Mårtensson et al 2009, Kumar et al 2011, Sharma & Prossnitz 2013, we have also ascertained that GPER1 mediates the glucose uptake induced by estrogens in CAFs and SKUT-1 cells.…”
Section: Discussionmentioning
confidence: 68%
“…Results from previous studies have indicated that estrogens increase insulin sensitivity and stimulate glucose uptake upon acute and chronic exposure to these steroids in target tissues as well as in ESR1-positive breast cancer cells (Alonso et al 2006, Moreno et al 2010, Garrido et al 2013. On the basis of these findings and considering that GPER1 has been shown to be involved in insulinregulated metabolic functions in both mice and humans (Mårtensson et al 2009, Kumar et al 2011, Sharma & Prossnitz 2013, we have also ascertained that GPER1 mediates the glucose uptake induced by estrogens in CAFs and SKUT-1 cells.…”
Section: Discussionmentioning
confidence: 68%
“…Plasma 17β-estradiol values obtained during the study were previously published in recent papers of our group (Moreno et al 2010;Pérez et al 2011). The plasma level of 17β-estradiol was significantly higher in groups E and C than in group O at all time points.…”
Section: General Characteristics Of Experimental Animalsmentioning
confidence: 55%
“…Our result is compatible with the previous study using Sprague-Dawley rats that demonstrated that the absence of ovarian hormone, particularly estrogen, had no influence on GLUT-4 protein 63 ; even though the other study using Wistar rats indicated a different result on the effect of ovariectomy on GLUT-4 expression. 64 Perhaps different animal models lead to different results. The relationship between GlcN and GLUT-4 was rarely discussed.…”
Section: Discussionmentioning
confidence: 99%